The effect of oat silage replacement with wheat straw in dairy cow diets on animal performance, rumen fermentation and adequacy of CPM dairy model predictions - Swiegers, Johannes Pieter (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhDAgric (Animal Sciences))--Stellenbosch University, 2011.